The Role of the NYPE Inter-Club Agreement as a Modular Apportionment Mechanism for Cargo-Claims across Multiple Jurisdictions - Allagan, Tiurma Mangihut Pitta; Bayuputra, M. Rizky (UI Scholars Hub, 2021)
The New York Produce Exchange Inter-Club Agreement (the 'ICA') is a staple maritime cargo claims provision incorporated into popular charter party forms, the NYPE46, ASBATIME, and NYPE15. It mechanically regulates cargo liability apportionment between charterers and shipowners mechanically for quick dispute resolution. This study aimed to examine the use and application of the ICA through a private international law lens to evaluate the ICA’s choice of law (being English law). ICA is an independent contract applicable to national legislation or any international convention, such as the Hague Rules, Hague-Visby Rules, and Hamburg Rules. It protects the commercial interests of shipowners and charterers and accommodates mandatory rules imposed by each jurisdiction. Furthermore, the popularity of ICA throughout the maritime industry as an apportionment mechanism was also determined by evaluating previous cases handled by English, Australian, and American Federal courts. Its importance in solving inconsistencies within maritime law on cargo apportionment and the perspective of ICA under the private international conflict of laws were also examined. Library research Involved studying conventions, statutes, and well-established cases of conflict of laws, private international law, cargo claims, and the ICA.